PLANT ANATOMY Smallanthus Sonchifolius (Poeppig & Endlicher) H. Robinson AND Tithonia Diversifolia (Hemsley) A. Grays AS REDUCING SUGAR CONTENT - Hery Setiyawan; Ana Mardiyaningsih; Juwari Juwari (Journal of Biotechnology and Natural Science, 2026)
Currently, the number of people with diabetes mellitus worldwide is increasing. According to the 11th edition of the International Diabetes Federation (IDF) Diabetes Atlas (2024/2025), approximately 19.5–20.4 million Indonesian adults will be living with diabetes by 2025. The plants Smallanthus Sonchifolius (Poeppig & Endlicher) H. Robinson and Tithonia Diversifolia (Hemsley) A. Gray are currently the subject of public discussion due to their usefulness in lowering blood sugar levels. The purpose of this study was to distinguish the macroscopic and microscopic identification characteristics and the presence of chemical compounds in the roots, stems, and leaves of Smallanthus Sonchifolius (Poeppig & Endlicher) H. Robinson and Tithonia Diversifolia (Hemsley) A. Gray. The research method was purely experimental, involving macroscopic identification characteristics, microscopic characteristics, and chemical testing of Smallanthus Sonchifolius (Poeppig & Endlicher) H. Robinson and Tithonia Diversifolia (Hemsley) A. Gray plants. Results and Discussion Macroscopic identification characteristics of Smallanthus Sonchifolius (Poeppig & Endlicher) H. Robinson and Tithonia diversifolia (Hemsley) A. Gray, which have taproots, round stems that are moist, soft, and woody, leaves with wavy edges, and alternate or opposite leaf arrangement, with some being scattered. Microscopic identification characteristics show the presence of calcium oxalate crystals. The chemical content of the leaves, bark, and roots of Smallanthus Sonchifolius (Poeppig & Endlicher) H. Robinson and Tithonia diversifolia (Hemsley) A. Gray contains saponins, polyphenols, flavonoids, and alkaloids, indicating that flavonoids act as antioxidants that can increase insulin sensitivity.Conclusion: The macroscopic and microscopic identification characteristics of the plants Smallanthus Sonchifolius (Poeppig & Endlicher) H. Robinson and Tithonia diversifolia (Hemsley) A. Gray are taprooted and tuberous, with brown taproots and no tubers, round stems that are soft, moist, and sometimes woody. The leaves have wavy edges, an opposite and alternate arrangement, and are scattered. The presence of epidermis, stomata, parenchyma, sclerenchyma, trichomes, and vascular bundles can be seen in the cross-section of the stem and leaves. The chemical content includes saponins, flavonoids, polyphenols, and alkaloids.